Mediation of Knowledge Management on the Effect of Human Resource Management Practices to Innovation Capability - Li, Xueqiang; Borromeo, Alyssa (International Journal of Global Economics and Management, 2024)
This study aimed to investigate the innovation capability in IT small and medium-sized enterprises (SMEs) in depth, with a key focus on human resource management practices, and knowledge management. Nowadays, managers recognize the value of knowledge as an intangible asset which stimulates innovation in organizations. However, few studies examine the role of human resource management in fostering knowledge capability which eventually leads to innovation. For this reason, this paper investigates the impacts of knowledge management in the relationship between the policies and practices of human resource management and innovation. The study is empirically based on the primary data collected from 130 IT small and medium-sized companies that are registered to Haidian District, one of the most important information technology industry base areas of Beijing, China. Data obtained from questionnaires will be analyzed through the SPSS statistical packet. The General Linear Mediation Regression test is used to measure the significance of the mediation effect of knowledge management capability. This study suggests that the innovation capability of IT SMEs may come from many aspects, and there is a certain degree of uncertainty that requires further exploration and research.